2009
DOI: 10.1021/ol902642z
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)/Copper(I)-Catalyzed Aza-Michael Addition/Click Reaction of in Situ Generated α-Azidohydrazones: Synthesis of Novel Pyrazolone−Triazole Framework

Abstract: A one-pot Cu(II)-catalyzed aza-Michael addition of trimethylsilyl azide to 1,2-diaza-1,3-dienes and Cu(I)-catalyzed 1,3-dipolar cycloaddition of in situ generated alpha-azidohydrazones with alkynes is reported. This process combining two consecutive steps with recycling of the catalyst (Cu(OAc)(2).H(2)O) represents a useful protocol for the smooth synthesis of novel pyrazolone-triazole derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…[109] This methodology also established the dual role of the copper catalyst in catalyzing both steps. [109] This methodology also established the dual role of the copper catalyst in catalyzing both steps.…”
Section: Azide Formation Via Miscellaneous Processesmentioning
confidence: 92%
See 1 more Smart Citation
“…[109] This methodology also established the dual role of the copper catalyst in catalyzing both steps. [109] This methodology also established the dual role of the copper catalyst in catalyzing both steps.…”
Section: Azide Formation Via Miscellaneous Processesmentioning
confidence: 92%
“…Recently an interesting three‐component methodology transforming 1,2‐diaza‐1,3‐dienes 53 into α‐triazole hydrazones 54 (R 4 =H)/ 54′ (R 4 =TMS) has been established as an aza‐Michael‐CuAAC sequence via α‐azidohydrazone formation (Scheme ) 109. This methodology also established the dual role of the copper catalyst in catalyzing both steps.…”
Section: Cuaac‐mcrs Initiated By Azide Generationmentioning
confidence: 99%
“…Incorporation of all five atoms of the DD skeleton into pyrazolone structures has been successfully applied in our previous work. 12 As four-atom diene synthons, DDs have found application in both [4+1] and [4+2] strategies for the synthesis of dihydropyrazoles 13 and pyridazines, 14 respectively. In addition, they can participate in formal [3+2]-, [4+2]-, and [5+2]-annulation reactions in which two or three ring atoms (C-C or C-C-N) of the azoene component are incorporated in the final cycloaddition products.…”
Section: Scheme 1 Reactivity Of αα'-Dioxothionesmentioning
confidence: 99%
“…During ongoing studies, we came to appreciate the advantages of diverse 1,2-diaza-1,3-dienes (DDs, 3; Figure 1). [11][12][13][14][15] In particular, we found that conjugated azoenes with electron-withdrawing substituents (e.g., esters or amides) on the terminal carbon and/or nitrogen (Figure 1), were particularly suitable as versatile synthetic building blocks because of their five-atom (3C + 2N) C4-electrophilic nature, dense substitution patterns, and flexible functionality that was capable of undertaking multiple roles. Generally, DDs can afford one to five atoms to construct cyclic molecules.…”
Section: Scheme 1 Reactivity Of αα'-Dioxothionesmentioning
confidence: 99%
“…Favi et al reported one‐pot copper (II)‐catalyzed Aza–Michael addition of trimethylsilyl azide to 1,2‐diaza‐1,3‐dienes and copper(I)‐catalyzed 1,3‐dipolar cycloaddition of the in situ generated α ‐azido hydrazones with alkynes . However, alkynes are the most commonly used starting materials that can provide a carbon framework.…”
Section: Introductionmentioning
confidence: 99%